Możliwości wpływu programów pomocowych na zmianę struktury zatrudnienia w rolnictwie Pomorza Zachodniego - Mickiewicz, Paweł (Possibilities of the Influence of Aid Programmes on the Change of Employment Structure in West Pomerania Agriculture, 2006)
The aim of this paper is to present the influence of aid programmes on the change of employment structure in West Pomeranian agriculture. The paper focuses on activity 2.3 in the frame of Integrated Operational Programme of Regional Development. The difficulties of implementation and realization of the program, from the moment of financial funds gathering, are described. The monographic method as well as the interview method are used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 111-117